2009
DOI: 10.1136/jmg.2009.069971
|View full text |Cite
|
Sign up to set email alerts
|

Karyomapping: a universal method for genome wide analysis of genetic disease based on mapping crossovers between parental haplotypes

Abstract: The use of genome wide single nucleotide polymorphism (SNP) arrays for high resolution molecular cytogenetic analysis using a combination of quantitative and genotype analysis is well established. This study demonstrates that by Mendelian analysis of the SNP genotypes of the parents and a sibling or other appropriate family member to establish phase, it is possible to identify informative loci for each of the four parental haplotypes across each chromosome and map the inheritance of these haplotypes and the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
307
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(314 citation statements)
references
References 31 publications
2
307
0
5
Order By: Relevance
“…The exact recombination rates approaching the telomeric ends may not be available or reliable from published studies, and in this case the rates of the full region surrounding the gene were not. With the use of technologies which rely upon whole genome amplification and SNP array based analysis, the significant locus dropout from WGA may also prevent the identification of crossovers between the nearest available SNP marker and the mutation [15,16]. In the case presented here, a misdiagnosis rate of 21 % was identified as a result of excessive STR marker distances, with respect to the mutation locus, failing to detect recombination and inappropriately assuming ADO at the mutation locus.…”
Section: Discussionmentioning
confidence: 90%
“…The exact recombination rates approaching the telomeric ends may not be available or reliable from published studies, and in this case the rates of the full region surrounding the gene were not. With the use of technologies which rely upon whole genome amplification and SNP array based analysis, the significant locus dropout from WGA may also prevent the identification of crossovers between the nearest available SNP marker and the mutation [15,16]. In the case presented here, a misdiagnosis rate of 21 % was identified as a result of excessive STR marker distances, with respect to the mutation locus, failing to detect recombination and inappropriately assuming ADO at the mutation locus.…”
Section: Discussionmentioning
confidence: 90%
“…20 SNP array comprises CN profiling and genome-wide haplotyping, enabling detection of both chromosomal imbalances and monogenic disorders. [25][26][27] Thus, SNP array holds the potential of providing a universal, 'off-the-shelf' PGD platform, applicable to a wide variety of genetic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Using SNP arrays to obtain this level of information requires the additional SNP analysis of the couple undergoing IVF, and entail a high level of bioinformatics analysis. The groups who developed this type of technology gave their particular method specific names, such as "Parental support" [48,53], "Karyomapping" [51] or "siChilds" [50]. The rates of meiotic and mitotic abnormalities found using SNP arrays were in concordance with those found with aCGH: Johnson et al found 9/26 cleavage stage embryos to carry a meiotic abnormality while 15/26 carried a mitotic abnormality while they found no evidence in their data set of uniparental disomy [48].…”
Section: Single Nucleotide Polymorphism (Snp) Arraysmentioning
confidence: 99%
“…Single nucleotide polymorphism arrays (SNP arrays) can be used after WGA at the single cell level to trace the parental origin of a missing or extra chromosome, to differentiate between a trisomy of meiotic or mitotic origin, and has been used to assess the frequency of uniparental disomy in embryos [48,49]. It has also been used for extensive haplotyping around the site of mutations causing monogenic disease, and is therefore quite suitable to combine the diagnosis of monogenic diseases in embryos with PGS [50][51][52]. Using SNP arrays to obtain this level of information requires the additional SNP analysis of the couple undergoing IVF, and entail a high level of bioinformatics analysis.…”
Section: Single Nucleotide Polymorphism (Snp) Arraysmentioning
confidence: 99%